Design of Cognitive Conflict-Based Generative Learning LKPD on Fluid Material to Improve Critical Thinking Ability of Grade XI High School Learners - Anabel, Haura Fitri; Akmam, Akmam; Mufit, Fatni; Emiliannur, Emiliannur (PILLAR OF PHYSICS EDUCATION, 2025)
Learning in the twenty-first century places a strong emphasis on developing higher order thinking skills (HOTS), particularly critical thinking abilities, which are crucial for understanding physics. An essential part of preparing pupils is education with critical thinking skills through an active and planned learning process. In fact, in learning Physics, students have low critical thinking skills. This demonstrates that in order to solve this issue, the learning method must be innovative. One effective way is in the form of Learner Worksheets (LKPD) by applying creative and innovative learning models. LKPD helps facilitate the learning process through structured guidance, motivate students to learn actively, improve concept understanding and critical thinking skills. This study employs the 4D development model and the R&D approach. With an Aiken'V of 0.93, the validity analysis's findings demonstrated the validity of the Generative Learning LKPD Based on Cognitive Conflict on Fluid Material. The next stage of the practicality test produced by educators was very practical at 89%. The practicality test produced by the user is very practical at 90%. Based on the study's findings, it can be said that the LKPD generated has demonstrated a sufficient degree of validity and applicability. Thus, it is determined that the use of Cognitive Conflict-Based Generative Learning (LKPD) on Fluid Material is employed and is amenable to further testing.